Enhancing Balanced Nutrition Literacy among Guidance and Counseling Teachers for the Prevention of Obesity in Secondary School Students - Nyono Dedi Prabowo; Yoanita Indra Kumala Dewi; Mifta Wahyu Rafa Sakina (Universitas Islam Negeri Raden Mas Said Surakarta, 2025)
Double-burden malnutrition is a major issue in Indonesia, with obesity rates rising over the past decade, especially among women of productive age and adolescents. This community service program aimed to improve nutritional literacy on balanced diets and obesity prevention among 252 secondary school guidance and counseling teachers (guru BK) from five districts/cities in East Java (Kediri, Tulungagung, Blitar, Trenggalek, and Madiun), empowering them to promote healthy eating and prevent obesity in students. Using a Participatory Action Research (PAR) approach with interactive lectures and group discussions, the program focused on the Ministry of Health's